Nail psoriasis: a questionnaire‐based survey. (13th August 2013) - Klaassen, K.M.G.; van de, P.C.M.; Pasch, M.C.
<x xml:space="preserve">Abstract</x> What's already known about this topic? The reported prevalence of nail psoriasis varies between 10% and 81%. Clinical manifestations depend on the involvement of the nail matrix and/or nail bed. Psoriatic arthritis is more prevalent in patients with nail psoriasis. What does this study add? We provide accurate prevalence rates of nail psoriasis, and insight into the association between nail psoriasis and different types of psoriasis. This is the first article to present patients' experiences of the effects of psoriasis therapies on nail lesions.